2017
DOI: 10.3168/jds.2016-12399
|View full text |Cite
|
Sign up to set email alerts
|

Production of benzoic acid as a natural compound in fermented skim milk using commercial cheese starter

Abstract: In this study, we investigated the production of natural benzoic acid (BA) in skim milk fermentation by 5 kinds of commercial cheese starters. Five kinds of starter were inoculated into 10% reconstituted skim milk, and then the culture was incubated at 2-h intervals for 10 h at 30, 35, and 40°C. In fermentation by MW 046 N+LH 13, the starter for making raclette, BA was highly detected after 8 h at 30 and 35°C. In fermentation by LH 13, the starter for making berg, BA steadily increased and was highly detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Lactic acid bacteria are reported to be isolated from some oat samples (Zhang et al, ), and oxidation of benzaldehyde produced by lactic acid bacteria may contribute to benzoic acid generation. (Park, Yoo, Paik, & Lim, ). Benzaldehyde was found in all oat samples but its oxidation was discovered in only one sample; this indicated that most samples were uncontaminated by the bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactic acid bacteria are reported to be isolated from some oat samples (Zhang et al, ), and oxidation of benzaldehyde produced by lactic acid bacteria may contribute to benzoic acid generation. (Park, Yoo, Paik, & Lim, ). Benzaldehyde was found in all oat samples but its oxidation was discovered in only one sample; this indicated that most samples were uncontaminated by the bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Phenol was only discovered in SW‐g with a low content. Although oats are a good source of phenols (Park et al, ), most of them are unable to be extracted by methods used in this research.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, benzoic acid also occurs naturally in several foods such as fruits, vegetables, spices and nuts. It is also found in low concentrations in dairy products as it is produced by micro-organisms during fermentation [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several adverse effects, such as metabolic acidosis, asthma, urticaria, hyperpnoea and convulsions have been observed in sensitive individuals even when present at low doses [ 8 , 9 ]. The Joint FAO/WHO (Food and Agriculture Organization of the United Nations/World Health Organization) Expert Committee on Food Additives evaluated and established 5 mg per kg of body weight as the acceptable maximum daily intake for benzoic acid and benzoate salt [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation